Identification of a Stochastic Dynamic Model for Aircraft Flight Attitude Based on Measured Data - Haiquan Li; Xiaoqian Chen; Jiatu Zhang; Bochen Wang; Jiahui Peng; Liang Wang (International Journal of Aerospace Engineering)
Stochastic disturbances are everywhere. The influence of stochastic factors on the modeling and simulation of aircraft flight dynamics should be considered. Therefore, a stochastic differential equation for aircraft flight attitude is modeled based on the traditional one in this paper. After that, an identification method based on the idea of sparse recognition for unknown parameters and stochastic disturbance is proposed. Finally, a set of measured flight data is used to verify that the identified stochastic model has obvious advantages over the traditional deterministic model when the aircraft is maneuvering in flight. This method can improve the accuracy and reliability of the aircraft flight dynamic model.